Impact of immobilized algae and its consortium in biodegradation of the textile dyes. Issue 6 (12th May 2023) - El-Sheekh, Mostafa M.; El Shafay, Shimaa M.; El-Shanshoury, Abd El-Raheem R.; Hamouda, Ragaa; Gharieb, Dalia Y.; Abou-El-Souod, Ghada W.
Abstract: In biological engineering, cell immobilization is a modern technique for immobilizing free cells in a small space. Disintegration and elimination of azo dyes [Reactive Orange 122 (orange 2RL) and Reactive Red 194 (Reactive Red M-2BF)] were investigated by using Chlorococcum sp. and Chlorococcum sp. mixed with Scenedesmus obliquus, respectively. After 7 days of incubation, the maximum decolorization was spotted at 40 ppm for Reactive Orange 122 and 20 ppm for Reactive Red 194 by Chlorococcum sp. and Chlorococcum sp. mixed with S. obliquus, respectively. The findings revealed that the best decolorization activity was found at pH 11 and 25 °C under aeration conditions. BG11 was considered the best medium for azo dye decolorization with a high decolorization percentage. Additionally, different concentrations of nitrogen and phosphorus show the high activity of decolorization of both dyes. Referring to vitamins (thiamin and Ascorbic acid), all studied concentrations showed high decolorization activity with immobilized Chlorococcum sp. mixed with S. obliquus ; however, different concentrations (20, 40, and 60 mg/l) of thiamin showed completely decolorization of Reactive Red 194 after 3 days, and 60 mg/l of ascorbic acid showed completely decolorization of Reactive Orange 122 after 5 days of inoculation. FT-IR and GC-Ms analysis for azo dyes after and before treatment with Immobilization of Chlorococcum sp. and Chlorococcum sp. mixed with Scenedesmus obliquus were detected. Novelty statement: The natural carrier algae and its consortium combined with a suitable immobilization technique were considered in this study, which is non-toxic, enhanced their bioremediation potential for dyes, and allowed multiple uses of biocatalysts. The novel use of the immobilization and its consortium of algae on the degradation efficiency of azo dyes and studying the effect of physicochemical conditions on decolorization and degradation of azo dyes. Application of immobilization techniques using microalgae could be excellent bioremediation of wastewaters.